The effects of auditor switching towards abnormal return in manufacturing company - Filmiar Yunida Nawangsari; Iswajuni Iswajuni (Asian Journal of Accounting Research, 2019)
The purpose of this paper is to examine the effects of simultaneous and partial auditor switching toward the abnormal return of manufacturing companies listed in Indonesia Stock Exchange between 2009 and 2012.Auditor switching is divided into some types: lateral Big 4 to Big 4 (B4B4), lateral non Big 4 to non Big 4 (NB4NB4), cross-up (CU) and cross-down. The abnormal return is measured with a market-adjusted model. In this study, company size is used as the control variable and is measured using the natural logarithm of the total assets (LnTA) and return on equity. Multiple linear regression is used for analysis with significant value a= 5 percent. The hypotheses were tested using f-test and t-test.The result shows that simultaneous auditor switchings affect the abnormal return. In partial auditor switching, only CU switch has effects on the abnormal return.This study provides additional literature on the effect of auditor switching, especially on an abnormal return.